Research on reliability allocation method for train network control system - HE Renwei; ZHAO Pu; ZHANG Xuefang (机车电传动)
The reliability design and allocation for train network control systems play a significant guiding role in evaluating the advantages and disadvantages of different options, identifying weak links affecting system reliability, and promoting design improvements. This study analyzed reliability requirements for train network control systems and investigated theoretical technologies for calculations related to network topology reliability. On this basis, a network topology state transfer model for the redundant architecture of train network control systems was developed, and a mathematical expression for network topology reliability calculations was deduced from the Markov process. Furthermore, a scoring-based reliability allocation method for system components were proposed, considering multiple influencing factors, including complexity, technical development levels, importance, and environmental conditions. Finally, the proposed reliability calculation and allocation method for train network control systems was verified, based on inputs from practical applications. This approach has proven beneficial for topology design in train network control systems according to their RAMS allocation indexes in real-world projects and offers a basis for rationality demonstration of RAMS design.